Medical treatment of infected, ulcerative infantile hemangioma covered with pseudomembrane - Alsmadi, Shadi A.; Megchelsen, Rebecca A.; Akintorin, Similolu M.; Byrd, Allison L.; Khilfeh, Manhal H. (International Journal of Contemporary Pediatrics, 2020)
Infantile hemangiomas (IH) are benign vascular tumors in children which usually spontaneously resolve. Although these tumors are common, very few require treatment. If treatment is required, the hemangioma can be treated medically or surgically. The case described in this article is unique as it depicts a neonate with a large ulcerative IH which presented with a pseudomembrane covering the entire surface of the lesion and was subsequently found to be infected with Pseudomonas aeruginosa. The hemangioma was treated medically rather than surgically, and the medical management of this tumor resulted in the involution of the lesion and the healing of the ulcer.